Autocalibrating Pulse Contour Analysis based on Radial Artery Applanation Tonometry for Continuous Non-Invasive Cardiac Output Monitoring in Intensive Care Unit Patients after Major Gastrointestinal Surgery—A Prospective Method Comparison Study. Issue 3 (May 2016) - Wagner, J. Y.; Langemann, M.; Schön, G.; Kluge, S.; Reuter, D. A.; Saugel, B.
The T-Line® system (Tensys® Medical Inc., San Diego, CA, USA) non-invasively estimates cardiac output (CO) using autocalibrating pulse contour analysis of the radial artery applanation tonometry–derived arterial waveform. We compared T-Line CO measurements (TL-CO) with invasively obtained CO measurements using transpulmonary thermodilution (TD-CO) and calibrated pulse contour analysis (PC-CO) in patients after major gastrointestinal surgery. We compared 1) TL-CO versus TD-CO and 2) TL-CO versus PC-CO in 27 patients treated in the intensive care unit (ICU) after major gastrointestinal surgery. For the assessment of TD-CO and PC-CO we used the PiCCO® system (Pulsion Medical Systems SE, Feldkirchen, Germany). Per patient, we compared two sets of TD-CO and 30 minutes of PC-CO measurements with the simultaneously recorded TL-CO values using Bland–Altman analysis. The mean of differences (± standard deviation; 95% limits of agreement) between TL-CO and TD-CO was −0.8 (±1.6; −4.0 to +2.3) l/minute with a percentage error of 45%. For TL-CO versus PC-CO, we observed a mean of differences of −0.4 (±1.5; −3.4 to +2.5) l/minute with a percentage error of 43%. In ICU patients after major gastrointestinal surgery, continuous non-invasive CO measurement based on autocalibrating pulse contour analysis of the radial artery applanation tonometry–derived arterial waveform (TL-CO) is feasible in a clinical study setting. However, the agreement of TL-CO with TD-CO and PC-CO observed in our study indicates that further improvements are needed before the technology can be recommended for clinical use in these patients.